Minimization of artifact protein aggregation using tetradecyl sulfate and hexadecyl sulfate in capillary gel electrophoresis under reducing conditions. Issue 13 (17th May 2020) - Guan, Qian; Atsma, Jennifer; Tulsan, Rekha; Voronov, Sergey; Ding, Julia; Beckman, Jeff; Li, Zheng Jian
Abstract: In the biopharmaceutical industry, CE‐SDS assesses the purity, heterogeneity, and stability of therapeutic proteins. However, for mAb‐1 and mAb‐2, typical CE‐SDS under reducing conditions produced atypical protein peak profiles, which led to biased purity results, thus were not acceptable for biologics manufacturing. This bias was caused by the formation of method‐induced higher molecular weight artifacts, the levels of which correlated with protein concentration. Here we show that adding sodium tetradecyl and hexadecyl sulfates to the sample and the sieving gel buffer solutions was required to prevent formation of aggregate artifacts and to maintain detergent:protein uniformity, suggesting their importance during the sample preparation steps of heat denaturation and subsequent cooling as well as during capillary migration. For these proteins, we show that this uniformity was likely due to the ability of these detergents to bind proteins with markedly higher affinities compared to SDS. "CE‐SC X S" methods (where CE‐SC X S is CGE using detergent composed of a sodium sulfate head group and a hydrocarbon tail, with "C X " representing various tail lengths), were developed with a sodium tetradecyl sulfate sample buffer and a sodium hexadecyl sulfate containing sieving gel buffer that minimized artifacts and provided robust characterization and release results for mAb‐1 and mAb‐2.